Knowledge about The Dangers of Smoking and Smoking Behavior of Students in Septembro Unamet 4th High school Dili, Timor Leste - Maximiano Oqui; Ning Arti Wulandari; Tonílio de Fátima dos Santos; Ana do Rosário de Jesus Leite (Journal of Ners and Midwifery, 2022)
Most adults who are dependent on nicotine start smoking in their teens. Timor-Leste is the country with the highest smoking rate in the world. Every year, more than 700 people in Timor-Leste are killed by tobacco-related diseases. Tobacco-related diseases are the fourth leading cause of death.  assessment to find out knowledge about the dangers of smoking and smoking behavior. This research design uses Crosssectional in high school with sample 122 student. Data collection was carried out by Quetionare. In this research the researchers conducted an assessment of knowledge about the dangers of smoking and smoking behavior. This study said out of 122 respondents, it was found that 59.8% had poor knowledge, 27.0% had normal knowledge and 13.1% and out of 122 respondents, 86.6% smoked and 48.3% of them had poor knowledge. The results of statistical tests showed that there was a relationship between knowledge about the dangers of smoking and smoking behavior in high school students. Solution to overcome the problem of knowledge about the dangers of smoking and smoking behavior is the provision of health education about the impact of smoking using methods that are attractive to high school students and carried out consistently.